2018
DOI: 10.1142/s0217751x18420058
|View full text |Cite
|
Sign up to set email alerts
|

Probing leptogenesis

Abstract: The focus of this chapter lies on the possible experimental tests of leptogenesis scenarios. We consider both leptogenesis generated from oscillations, as well as leptogenesis from out-of-equilibrium decays. As the Akhmedov-Rubakov-Smirnov (ARS) mechanism allows for heavy neutrinos in the GeV range, this opens up a plethora of possible experimental tests, e.g. at neutrino oscillation experiments, neutrinoless double beta decay, and direct searches for neutral heavy leptons at future facilities. In contrast, te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 400 publications
(689 reference statements)
1
130
0
Order By: Relevance
“…3 and 4 display the symmetry and reflection properties that we anticipated in Eq. (16). Our results are thus invariant under the different operations on the RHN Yukawa couplings shown in Eq.…”
Section: Numerical Parameter Scanmentioning
confidence: 62%
See 2 more Smart Citations
“…3 and 4 display the symmetry and reflection properties that we anticipated in Eq. (16). Our results are thus invariant under the different operations on the RHN Yukawa couplings shown in Eq.…”
Section: Numerical Parameter Scanmentioning
confidence: 62%
“…Our results are thus invariant under the different operations on the RHN Yukawa couplings shown in Eq. (16). In particular, we observe that the dependence of δM max on z R is mostly controlled by the sin (2z R ) term in Eq.…”
Section: Numerical Parameter Scanmentioning
confidence: 67%
See 1 more Smart Citation
“…Such peak searches have been performed and are known to reach deep into the region [33] where leptogenesis is feasible in the νMSM [15,34,35]. An interesting point in this context is the extremely good mass resolution, of order of few MeV, which would allow to test the leptogenesis hypothesis [36] in part of the parameter space [37][38][39] if any HNLs are discovered. The…”
Section: Jhep07(2018)105mentioning
confidence: 99%
“…Recently, NOs experiments have shown that the mixing-angle θ 13 is non zero [35] and also suggest the possibility of CP violation in the light neutrino sector [36]. However, extra sources of CP violation are needed in order to explain the BAU via Leptogenesis (see [37] for a review). In addition, when heavy neutrino masses are below the electroweak scale (M N < 246 GeV), the BAU is generated via CP-violating of Heavy Neutrino Oscillations (HNOs) during their production [38].…”
Section: Introductionmentioning
confidence: 99%